Private Participation in the Transmission and Distribution of Natural Gas : Recent Trends - Izaguirre, Ada Karina (World Bank, Washington, DC, 2012)
This paper examines the increasing participation of the private sector in the transmission and distribution of natural gas in developing countries during the 1990s, resulting mainly from the growing demand for new gas transport facilities coinciding with a growing consensus in favor of private participation in infrastructure. This note, drawing on the bank's PPI (Private Participation in Infrastructure) Project database, provides an overview of the patterns and trends in the projects in the twenty six developing countries which introduced private participation in natural gas between 1990 and 1997. It concludes with the thought that growth in privately funded and operated export projects promise s to bring the economic and environmental benefits of natural gas to a larger number of countries.